Pengolahan Limbah Padat Menggunakan Teknologi Incinerator di Desa Pulo Ampel Kabupaten Serang Provinsi Banten - Utomo, Dhafid Wahyu; Syahputra, Ade Indra; Irawati, Irawati; Alim, Moebi Syahirul; Amalia, Choirunisa; Sidik, Ezis Japar (Jurnal Ilmiah Pangabdhi, 2024)
The increasing volume of waste due to human activities causes the need for waste processing efforts. One method that can be used to treat waste is the combustion method using incinerator technology. By using incinerator technology, the volume of waste can be reduced by up to 97% and reduce the weight of waste by up to 70%. In addition, the work of this incinerator can be reused like ash to make bricks and heat that can be used as a power plant. The work of gas that overcomes the problem of environmental pollution and can directly support the improvement of free air. Therefore, we conducted online training activities through google meetings on solid waste processing using incinerator technology in Pulo Ampel Village, Banten Province. With this training, it can add insight and knowledge, especially the people of Pulo Ampel Village about waste processing using incinerator technology.